Physical Effects of Cleaning Agents on Orthodontic Thermoplastic Retainer Polymer: A Narrative Review - Iman Azmuddin; Nik M. N. Mustapha; Hasnah B. S. G. Khan; Saraswathy D. Sinniah (Wolters Kluwer, 2024)
Indexed by WOS/ Scopus